L’Empire ottoman, cœur de l’anti-utopie kadaréenne - Jean-Paul Champseix (Cahiers Balkaniques)
For Ismail Kadare despotism and the East are synonymous. As the continuation of the tyrannical regimes of antiquity, the Ottoman Empire represents the spirit of blind and destructive conquest. Throughout Kadare's work the Sublime Porte, the seat of Ottoman power, seeks relentlessly to destroy Albania's European roots. However this Ottoman Empire with its anachronisms also brings the past to bear on the present. Communism is the true heir to Asiatic despotism. In his anti-utopian works, Kadare illustrates and condemns the perversity of an absolute power which comes to resemble pure evil.